Utility of Computerized Axial Tomography (CT) Investigation in Two-Week Wait Colorectal Referral Pathway During the COVID-19 Pandemic: A Retrospective Analysis - Bavikatte, Akshay; Keshavamurthy, Nivedita Shivane; Athisayaraj, Thomas (British Journal of Healthcare and Medical Research, 2024)
Introduction: Colorectal two-week wait pathway investigations have been majorly affected by Covid 19, especially with regard to endoscopy as well as virtual colonoscopy procedures in comparison to computerized tomography (CT) scans. We aimed to analyze the CT findings of patients referred along the week wait pathway at the height of the pandemic. Method: A total of 900 patients were referred via the straight-to-test pathway in 2020, from March to December, at the West Suffolk Hospital NHS Trust. A retrospective analysis of the CT scans of these patients was performed. Results: A total of 90 (10%) patients had a CT Scan as part of the initial workup.22 patients (24.4%) of the CT scan revealed malignancy. Among them, 18(60%) patients were diagnosed with primary colorectal tumors, and 4 (13%) patients had primary thoracic cancers. 8 (8.88%) showed metastatic disease on the scan. Among them, three (38%) were due to colorectal primary disease, and the remaining were diagnosed with widespread metastatic disease of unknown origin. The remaining patients were diagnosed with High grade B cell lymphoma, neuroendocrine tumor, pancreatic mass, and primary renal cell carcinoma. One patient had high grade small bowel obstruction due to a band adhesion resulting in emergency surgery and 5% of the patient needed a vascular referral for Abdominal aneurysm. Conclusion: CT scans in two-week colorectal referral patients play a significant role in the diagnosis of advanced disease. The ease of the procedure makes it more attractive during the pandemic in contrast to endoscopy and virtual colonoscopy, which have been significantly impacted by COVID 19.